Pengaruh Aktivitas Masyarakat Pesisir terhadap Keberlanjutan Cagar Alam Teluk Adang - Susanti, Rina (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
This study aimed to assess the effect of eople’s activities toward the sustainability of coastal mangrove Adang Bay conservation. Using a quantitative approach, the research try to identity through scoring, descritive statistical analysis which produces the measurement of coastal community’s activities most influence on changes in mangrove areas Adang Bay Nature Reserve. Trading and service activities, housing activity, industrial activity and seaports activity affect the sustainability of mangrove area Adang Bay Nature Reserve. The level of activity, are: (1) coastal pond. This activity provide better welfare than other activities; (2) Sea ort activities. Since it begin from significant development activities in line with technological developments; (3) Trading and servise activities. These activities as a sideline activity performed by most of the population in Pondong Baru; (4) Housing activities, for each migrants resident prefer to own their own home (property rights) so that the housing land requirement will be increased; and (5) industrial activities, since this activities can support other activities. Mangrove area Adang Bay Nature Reserve is influenced by three aspects: economy dominated by farming activities, socio-cultural aspects are dominated by sea port activities and aspects of the environment that is dominated by coastal pond activities.